Hydrogen borrowing catalysis using 1° and 2° alcohols: investigation and scope leading to α and β branched products - Frost, JR; Cheong, CB; Akhtar, WM; Caputo, DFJ; Christensen, KE; Stevenson, NG; Donohoe, TJ (Elsevier, 2021)
The alkylation of a variety of ketones using 1° or 2° alcohols under hydrogen borrowing catalysis is described. Initial research focused on the α-alkylation of cyclopropyl ketones with higher 1° alcohols (i.e. larger than MeOH), leading to the formation of α-branched products. Our search for additional substrates with which to explore this chemistry led us to discover that di-ortho-substituted aryl ketones were also privileged scaffolds, with Ph∗ (C6Me5) ketones being the optimal choice. Further investigations revealed that this motif was crucial for alkylation with 2° alcohols forming β-branched products, which also provided an opportunity to study diastereoselective and intramolecular hydrogen borrowing processes.